David Fairchild as a naturalist and advocate for tropical biology research: his 1924 trip to Panama - Morey, Valeria; Lahn, Eleanor; Elton, Charlotte; Ibáñez, Alicia; Basset, Yves; Franisco-Ortega, Javier (Webbia, 2025)
Plant explorer David Fairchild (1869–1954) and four prestigious American zoologists [Nathan Banks (1868–1953), Curt P. Richter (1894–1988), William M. Wheeler (1865–1937), and James Zetek (1886–1959)] gathered at the newly established Barro Colorado Island Laboratory in Panama to conduct field studies from late July to early August 1924. This visit occurred just weeks after this field station’s official inauguration. Fairchild traveled to Panama with his son, Graham B. Fairchild (1906–1994), and while returning from Panama to the U.S. aboard the SS Ulua, he prepared a 21-page handwritten narrative of this trip. This unpublished manuscript is housed at Fairchild Tropical Botanic Garden and has been transcribed here with annotations. A large component of the manuscript focuses on entomological findings, along with Fairchild’s advocacy and support for tropical biology studies. The document includes philosophical reflections that Fairchild made on human behavior and biological processes inspired by his entomological observations and discussions he had with biologists at the station. The document shows Fairchild as a broad-based naturalist who played a key role in the initial establishment of one of the most famous tropical field stations in the world. Fairchild carried plant material from Cuba (5 accessions, 5 species) and Panama (23 accessions, 20 species) on his trip back to the U.S. His narrative discusses technical challenges involved in transporting living material in Wardian cases. Entomological findings were published in two papers by Wheeler upon his return to the U.S. Fairchild delivered a talk on mangosteens (Garcinia sp., Clusiaceae) in Ancon a few days before his departure from Panama. During his stay in Panama, Fairchild also met with the curator of living collections of Summit Gardens, Holger P. Johansen (1898–1935), along with Panama Canal Zone governor Jay J. Morrow (1870–1937), orchid specialist and horticulturist Charles Wesley Powell (1854–1927), and Chief Sanitary Inspector J. B. Shropshire. A total of 46 photos taken by Fairchild were located during this study. In addition to these photographs, our research involved looking into newspaper reports from Panama and Cuba, as well as USDA germplasm inventories from 1924. The main botanical highlights recorded by Fairchild concern insect-plant interactions found between ants and the legumes Inga sp. and Vachellia melanoceras (Beurl.) Seigler & Ebinger, as well as the pollination biology of the orchid Catasetum viridiflavum Hook.